Kajian Kriminologi terhadap Pencurian Uang di Anjungan Tunai Mandiri di Rumah Sakit Leona Kefamenanu - Desanta Prasedis Tanu; Debi F.Ng.Fallo; Adrianus Djara Dima (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research is a study that aims to analyze the case of money theft at the automated teller machine of Leona Hospital, Kefamenanu Regency. This research is an empirical legal research supported by a qualitative descriptive approach using primary, secondary and tertiary data. The results of this study show that (1) The factors that cause the theft of money carried out by Security are internal factors and external factors. Internal factors are in the form of the intentions of the perpetrators, morals and education, while external factors are in the form of the living environment, economic conditions and global development. (2) In an effort to counteract restorative justice, restorative justice efforts are carried out so that the perpetrators who commit criminal acts do not undergo criminal proceedings, and thus, through joint deliberation, it is hoped that solutions and alternatives can be found to resolve criminal cases.